HLA Class II Genes HLA-DRB1, HLA-DPB1, and HLA-DQB1 Are Associated With the Antibody Response to Inactivated Japanese Encephalitis Vaccine - Yao, Yufeng; Yang, Huijuan; Shi, Lei; Liu, Shuyuan; Li, Chuanying; Chen, Jun; Zhou, Ziyun; Sun, Mingbo; Shi, Li (Frontiers in Immunology, 2019)
Aim: The objective of this study was to evaluate the association of the human leukocyte antigen (HLA) class II genes HLA-DRB1, HLA-DPB1, and HLA-DQB1 with the humoral immune response elicited by inactivated Japanese encephalitis (JE) vaccine (IJEV). Methods: A total of 373 individuals aged 3-12 years in the Inner Mongolia Autonomous Region in China, who received two doses of IJEV at 0 and 7 days, were enrolled in the current study. Based on the individuals’ specific JE virus (JEV)-neutralizing antibodies (NAbs), they were divided into a seropositive and a seronegative group. HLA-DRB1, HLA-DPB1, and HLA-DQB1 were genotyped using a sequencing-based typing method. Next, the association of the HLA class II genes and their haplotypes with antibody response was evaluated. Results: Based on NAbs, a total of 161 individuals were classified as seropositive and 212 as seronegative. DQB1*02:01 was significantly associated with JEV seropositivity (P < 0.001, OR = 0.364, 95% CI: 0.221-0.600), while DQB1*02:02 was significantly associated with JEV seronegativity (P = 5.03 × 10-6, OR = 7.341, 95% CI: 2.876-18.736). The haplotypes DRB1*07:01-DPB1*04:01-DQB1*02:01, DRB1*15:01-DPB1*02:01-DQB1*06:02, DRB1*07:01-DQB1*02:01, and DPB1*02:01-DQB1*06:02 were very frequent in the seropositive group, while DRB1*07:01-DPB1*17:01-DQB1*02:02, DRB1*07:01-DQB1*02:02, and DPB1*17:01-DQB1*02:02 were very frequent in the seronegative group. The presence of DRB1*01:01, DRB1*04:05, DRB1*09:01, DRB1*12:02, DRB1*13:02, and DRB1*14:01 was associated with a higher geometric mean titer (GMT) of NAbs than that of DRB1*11:01 at the DRB1 locus (P < 0.05). At the DPB1 locus, the presence of DPB1*05:01 was associated with higher GMTs than that of DPB1*02:01 and DPB1*13:01 (P < 0.05), and the presence of DPB1*04:01 and DPB1*09:01 was associated with higher GMTs than that of DPB1*13:01 (P < 0.05). Conclusions: The present study suggests that HLA class II genes may influence the antibody response to IJEV.